Iridium recovery method
By mixing and mixing carbon materials, carbides are formed at high temperatures, and the acid dissolution is used to separate iridium and zirconium dioxide, solving the separation difficulties caused by the combination of iridium and zirconium dioxide, and achieving efficient iridium recovery and purity Improved, reduced costs.
Patent Information
- Application Number
- CN202411194529.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-17
AI Technical Summary
During the laser crystal straight drawing process, iridium and zirconium dioxide are combined at high temperatures, which makes it difficult to separate and purify. The traditional wet purification method has problems of low recovery and high cost.
By crushing and mixing the insulating material containing iridium and zirconium dioxide with carbon materials, carbides are formed at high temperatures, and the properties of acid dissolution are used to separate iridium and zirconium dioxide, and then improving iridium through alkali melting and acid stewing and boiling. purity and recovery rate.
This method effectively improves the purity and recovery rate of iridium, shortens the separation and recovery process, reduces costs, and improves the overall recycling efficiency.
Smart Images

Figure CN119144841A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of precious metal recovery, and more specifically, relates to an iridium recovery method. Background Art
[0002] Iridium metal is rare and expensive, so the residues and scraps produced during the smelting and processing of iridium products, as well as the waste products after long-term use, need to be separated and purified before reuse; especially in the laser crystal pulling process, the long-term ultra-high ambient temperature causes the iridium crucible to evaporate a lot, and the crystals adhere to the surrounding zirconium dioxide insulation material as the furnace lining, causing the iridium crucible to lose 200g-300g of weight. Since iridium and zirconium dioxide are combined under high temperature treatment and have good chemical stability, it is difficult to separate the two. In addition, the overall mass of iridium only accounts for 1%-2% of the zirconium dioxide insulation material, so enrichment and purification are particularly difficult.
[0003] Traditional iridium recovery adopts wet purification method, which mainly uses peroxide and strong alkali to oxidize iridium into iridate at high temperature, and then adds hydrochloric acid or aqua regia to transfer iridium to the solution. Subsequently, chemical method is used to separate most of the impurity metals by oxidation precipitation of ammonium chloroiridate; reduction sulfidation removes a small amount of precious metals; and then oxidation precipitation into ammonium chloroiridate; finally, it is processed into iridium powder, chloroiridic acid, iridium chloride and other related products according to actual needs; because the iridium content in iridium-containing zirconium dioxide insulation material is relatively low, under high temperature and strong alkali conditions, zirconium dioxide will be converted into sodium zirconate, and will subsequently enter the solution with acid leaching, making subsequent purification difficult. Repeated oxidation, filtration, reduction and sulfidation are required, resulting in a large increase in low-concentration iridium solution, reducing the overall recovery rate. Summary of the invention
[0004] The main purpose of the present invention is to provide an iridium recovery method, which utilizes the property of zirconium oxide and carbon to be reduced at high temperature to form carbides, and the property that zirconium carbide is soluble in oxidizing acids to separate iridium and zirconium dioxide insulation materials, and recover iridium simply and directly.
[0005] According to a first aspect of the present invention, there is provided an iridium recovery method, comprising the following steps:
[0006] Step 1: crushing and grinding the thermal insulation material containing iridium and zirconium dioxide to obtain powder;
[0007] Step 2: Mixing the powder and the carbon material to obtain a mixed powder;
[0008] Step 3: heating the mixed powder under vacuum conditions so that the metal elements except iridium form carbides to obtain a carbide mixture;
[0009] Step 4: dissolving the carbonized mixture in acid, filtering, and obtaining a first filter residue; the first filter residue contains iridium element.
[0010] The present invention carbonizes and acid-dissolves the thermal insulation material containing iridium and zirconium dioxide, and utilizes the characteristic that other metal elements are easily carbonized by carbon materials, so that other metal elements can be acid-dissolved in step 4, which can effectively improve the purity of iridium and reduce the loss of iridium.
[0011] Preferably, the acid used for acid dissolution can be hydrochloric acid, nitric acid or phosphoric acid.
[0012] Preferably, the mass ratio of the powder to the carbon material is 2 to 6:1.
[0013] Preferably, the mass ratio of the powder to the carbon material is 3 to 5:1.
[0014] In the above iridium recovery method, the first filter residue is alkali-melted, acid-leached, and filtered to obtain a second filter residue, which is the iridium finished product.
[0015] Preferably, the first filter residue is dried, powdered sodium hydroxide is added in a mass ratio of 1:1 to 5, and roasted under air at a temperature of 300° C. to 400° C. for 1 to 3 hours, and then cooled and taken out to obtain a roasted mixture;
[0016] The roasted mixture was added into hydrochloric acid with a mass concentration of 36% for acid leaching, transferred into a beaker, boiled for 1 to 2 hours, cooled and filtered to obtain a second filter residue.
[0017] In some implementation cases of the present invention, the mass ratio of the powdered sodium hydroxide to the first filter residue may be 1:1, 1:2, 1:3, 1:4, 1:5;
[0018] In some embodiments of the present invention, the calcination temperature can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 375°C, 380°C, 385°C, 390°C, or 400°C.
[0019] Preferably, the mass ratio of the first filter residue to powdered sodium hydroxide is 1:3.
[0020] Preferably, the calcination temperature is 380°C to 390°C.
[0021] In the above iridium recovery method, alkaline solution is added to the filtrate obtained by filtration in step 4, the pH value is adjusted to 2-4, and the first precipitate is obtained by filtration; the first precipitate contains zirconium element.
[0022] Preferably, the alkali solution is aqueous ammonia, the volume ratio of the filtrate to the aqueous ammonia is 1:1, and the first precipitate is hydrolyzed and precipitated at a temperature of 40° C. to 80° C., wherein the first precipitate includes zirconium hydroxide.
[0023] Preferably, the pH is adjusted to 2-2.5.
[0024] Preferably, the first precipitate is hydrolyzed and precipitated at a temperature of 70°C to 80°C.
[0025] In the above-mentioned iridium recovery method, the filtrate from which the first precipitate is filtered out is added with acid solution, and filtered to obtain a second precipitate; the second precipitate contains yttrium element.
[0026] Preferably, the acid solution is a 1 mol / L oxalic acid aqueous solution, and a second precipitate is precipitated at a temperature of 60° C. to 80° C., wherein the second precipitate includes yttrium oxalate.
[0027] Preferably, in step 1, the thermal insulation material is ground to 200-400 meshes.
[0028] Preferably, in step 2, the powder is mixed with the carbon material and ball-milled.
[0029] Preferably, the carbon material is hydrophobic graphite;
[0030] Preferably, in step 3, the mixed powder is placed in a graphite crucible and heated in a vacuum induction melting furnace;
[0031] During heating, the temperature is raised to 1000°C-1300°C, kept at this temperature for 30 minutes, then raised to 1400°C-1600°C, kept at this temperature for 30 minutes, and then an inert gas is introduced to cool the mixture to obtain a carbonized mixture.
[0032] Preferably, in step 4, the carbonized mixture is poured into a container filled with pure water, the carbon material is removed by decanting and filtering, and then acid dissolution is performed.
[0033] Preferably, during acid dissolution, a sulfuric acid solution with a mass concentration of 20% to 50% is first added, heated in a water bath to 60° C. to 90° C., and a hydrogen peroxide solution with a mass concentration of 30% is slowly dripped in to obtain a solid-liquid mixture;
[0034] The solid-liquid mixture is heated to boil, and maintained in a slightly boiling state for not less than 30 minutes, and then cooled and filtered to obtain a first filter residue.
[0035] Preferably, a sulfuric acid solution with a mass concentration of 30% to 40% is used.
[0036] Preferably, after adding the sulfuric acid solution, the mixture is heated in a water bath to 70° C. to 75° C.
[0037] One of the above technical solutions of the present invention has at least one of the following advantages or beneficial effects:
[0038] The present invention mixes iridium-containing zirconium dioxide powder with a carbon material, reduces zirconium dioxide to generate zirconium carbide at high temperature by virtue of the reducing property of the carbon material, and obtains a mixture of iridium, zirconium carbide and yttrium carbide, dissolves the zirconium carbide and yttrium carbide by acid dissolution, and obtains a crude iridium-containing product after filtering;
[0039] Subsequently, a small amount of residual zirconium oxide is removed by melting sodium hydroxide, and zirconium oxide and sodium hydroxide generate sodium zirconate, which is finally removed by boiling with hydrochloric acid, filtered, cleaned and dried to obtain the finished iridium powder. The material properties are fully utilized to ensure that iridium is highly inert during the entire reaction process, which greatly shortens the entire separation and recovery process and improves the overall recovery rate.
[0040] Moreover, by adding ammonia water to adjust the pH value of the sulfuric acid solution containing zirconium and yttrium, zirconium sulfate can be hydrolyzed and precipitated into zirconium hydroxide. Yttrium oxalate can be precipitated by adding oxalic acid to the mother liquor after filtration. Most of the valuable metals can be recovered through simple precipitation, filtration and washing operations, thereby improving the economy of the entire recovery process and reducing the recovery cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The present invention is further described below in conjunction with the accompanying drawings and embodiments;
[0042] Figure 1 It is a process flow chart of the iridium recovery method of the present invention. DETAILED DESCRIPTION
[0043] The embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals represent the same or similar elements or elements having the same or similar functions from beginning to end. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0044] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.
[0045] Example 1
[0046] Reference Figure 1 , an iridium recovery method, comprising the following steps:
[0047] Step 1: Place 40.24 kg of thermal insulation materials containing iridium and zirconium dioxide in a tungsten carbide jaw crusher and crush them three times until the particle size of the material is below 10 meshes; the jaw head and jaw plate are made of tungsten carbide, which has a higher hardness than zirconium dioxide. During the crushing process, there will be no material damage due to extrusion and friction, thereby avoiding secondary pollution of the raw materials;
[0048] 5.02 kg was taken out and ground into 300-400 meshes in a tungsten carbide disc grinder. The grinder can use tungsten carbide, zirconium oxide and other materials as the working chamber. After sieving, 1.02 kg of iridium-containing zirconium dioxide powder was sieved out with a 300-mesh sieve. The powder contained 11.83 g of iridium, 84.28 wt% of zirconium oxide and 14.55 wt% of yttrium oxide.
[0049] Step 2: Take 0.40 kg of hydrophobic graphite, the mass ratio of powder to graphite is 2.5:1, mix the iridium-containing zirconium dioxide powder with graphite and ball-mill, use a 360-degree omnidirectional ball mill for ball milling, the grinder can use tungsten carbide, zirconium oxide and other materials as the working chamber, mix and run in the 360-degree omnidirectional ball mill for 30 minutes, and take out after standing.
[0050] Step 3: Add the mixed powder into a graphite crucible with a perforated lid and heat it in a vacuum induction melting furnace with a pressure of less than 10 -2 Pa; when heating, the temperature is raised to 1200°C-1300°C, kept warm for 30 minutes, then raised to 1500°C, kept warm for 30 minutes, the heating and vacuum systems are turned off, argon gas is introduced to cool down, and the mixture is cooled to room temperature; a carbonized mixture containing graphite, iridium, zirconium carbide and yttrium carbide is obtained.
[0051] Step 4: Pour the carbonized mixture into a container filled with 500 ml of pure water, and remove the graphite by filtration until the upper liquid is clear; the graphite can be dried and recycled;
[0052] Continue to add 2800 ml of 40% sulfuric acid solution into the container, heat it in a water bath to 70°C to 75°C, and drop 1500 ml of 30% hydrogen peroxide solution at a rate of 1.0 ml / s to obtain a solid-liquid mixture;
[0053] The solid-liquid mixture is heated to boil, maintained at a slight boiling state for 45 minutes, cooled and filtered, the filter residue is a crude product containing iridium, and the filtrate is a sulfuric acid solution containing zirconium and yttrium.
[0054] The filter residue is dried, 35 g of powdered sodium hydroxide is added at a mass ratio of 1:3, the mixture is placed in an alumina crucible, and the mixture is roasted in an atmosphere furnace. Air is injected during the roasting process to assist the melting process and oxidize and remove the carbon material. The roasting temperature is 380° C. to 390° C., and the mixture is roasted for 3 hours. The zirconium oxide and the sodium hydroxide generate sodium zirconate. The mixture is cooled to room temperature and taken out to obtain a roasted mixture.
[0055] Add 50 ml of 36% hydrochloric acid to the roasted mixture for leaching, transfer it to a beaker, add 50 ml of 36% hydrochloric acid again, heat and keep it slightly boiling for 1 hour, boil it with hydrochloric acid to remove sodium zirconate, cool it down, filter it, wash it with pure water, and dry it to obtain the iridium product.
[0056] At the same time, add ammonia water with a volume ratio of 1:1 to the filtrate obtained in step 4 to adjust the pH to 2-2.5, heat to 70°C-80°C, hydrolyze and precipitate zirconium hydroxide, filter to obtain the zirconium hydroxide precipitate, and dry to obtain the industrial crude zirconium hydroxide.
[0057] Add about 2.5L of 1mol / L oxalic acid aqueous solution to the filtrate from which the zirconium hydroxide precipitate is removed, ensuring an excess of 30% to 40%, and obtain yttrium oxalate precipitate at a temperature of 60°C to 80°C, which is filtered and dried to obtain an industrial crude yttrium oxalate product.
[0058] Example 2
[0059] Different from Example 1, in step 2, the carbon material is activated carbon, and the activated carbon is mixed with the powder and ball-milled.
[0060] Example 3
[0061] The difference from Example 1 is that in step 2, the carbon material is carbon black, and the carbon black is mixed with the powder and ball-milled.
[0062] Example 4
[0063] Different from Example 1, in step 2, the mass ratio of powder to graphite is 5:1, and the amount of graphite is 0.20 kg.
[0064] Example 5
[0065] Different from Example 1, in step 2, the mass ratio of powder to graphite is 2:1, and the amount of graphite is 0.51 kg.
[0066] Example 6
[0067] The difference from Example 1 is that in step 4, during the acid dissolution, the acid used is hydrochloric acid with a mass concentration of 18%, and 2800 ml of hydrochloric acid with a mass concentration of 18% is poured into the container.
[0068] Example 7
[0069] The difference from Example 1 is that in step 4, 11.7 g of powdered sodium hydroxide is added at a mass ratio of 1:1.
[0070] Example 8
[0071] The difference from Example 1 is that in step 4, 58.3 g of powdered sodium hydroxide is added at a mass ratio of 1:5.
[0072] Example 9
[0073] Different from Example 1, in step 4, the calcination temperature is 300°C to 375°C.
[0074] Example 10
[0075] Different from Example 1, in step 4, the calcination temperature is 385°C to 400°C.
[0076] Comparative Example 1
[0077] Step 1 is the same as in Example 1;
[0078] Step 2: Pour the zirconium dioxide powder into a container filled with 500 ml of pure water, continue to add 2800 ml of 40% sulfuric acid solution into the container, heat it in a water bath to 70°C to 75°C, and drop 1500 ml of 30% hydrogen peroxide solution at a rate of 1.0 ml / s to obtain a solid-liquid mixture;
[0079] The solid-liquid mixture is heated to boil, maintained at a slight boiling state for 45 minutes, cooled and filtered, the filter residue is a crude product containing iridium, and the filtrate is a sulfuric acid solution containing zirconium and yttrium.
[0080] The filter residue is dried, and powdered sodium hydroxide is added in a mass ratio of 1:3, placed in an alumina crucible, and roasted in an atmosphere furnace, and air is injected during the roasting process; the roasting temperature is 380°C to 390°C, and the roasting is performed for 3 hours, and zirconium oxide and sodium hydroxide generate sodium zirconate, which is cooled to room temperature and taken out to obtain a roasted mixture;
[0081] The roasted mixture is added with 36% hydrochloric acid for leaching, transferred to a beaker, and 36% hydrochloric acid is added again, heated to keep slightly boiling for 1 hour, and the hydrochloric acid is boiled to remove the sodium zirconate, cooled and filtered, washed with pure water, and dried to obtain the iridium product.
[0082] Recovery results analysis
[0083] The weight of the iridium finished products recovered in Examples 1-10 and Comparative Example 1 and the purity of the iridium finished products were respectively detected. The purity of the iridium finished products can be detected by ICP-OES.
[0084] Table 1
[0085] Iridium finished product weight (g) Iridium finished product purity Example 1 11.61 >99.9% Example 2 11.71 >99.5% Example 3 11.65 >99.5% Example 4 11.77 >99.5% Example 5 11.64 >99.9% Example 6 11.81 >99.0% Example 7 11.73 >99.5% Example 8 11.62 >99.9% Example 9 11.69 >99.5% Example 10 11.45 >99.9% Comparative Example 1 21.28 <60%
[0086] By comparing Examples 1 to 3, it can be seen that the iridium products obtained by using other carbon materials are more than those obtained by using graphite, but the purity of the iridium products is poorer, and the iridium products obtained by using graphite have the best purity;
[0087] By comparing Examples 1, 4 and 5, it can be seen that the proportion of graphite added will affect the final iridium product. If the proportion of graphite added is small, zirconium and yttrium may not be completely carbonized, and the purity of the final iridium product is poorer; if more graphite is added, the reduction effect is better, and the effect of removing zirconium and yttrium is better;
[0088] Comparing Examples 1 and 6, it can be seen that when other acids are used, the zirconium carbide and yttrium carbide are not fully dissolved, and the purity of the iridium product finally obtained is poorer;
[0089] Comparing Examples 1, 7 and 8, it can be seen that the ratio of added sodium hydroxide affects the final iridium product. When the ratio of sodium hydroxide is low, the melting is not complete, and the purity of the final iridium product is poor. When the ratio of sodium hydroxide is high, the melting is sufficient, and the effect of removing the remaining zirconium is better.
[0090] Comparative Examples 1, 9 and 10, it can be seen that the roasting temperature in step 4 will affect the final iridium finished product. When the roasting temperature is insufficient, the melting is not thorough, and the purity of the iridium finished product finally obtained is worse. When the roasting temperature is too high, there is a certain corrosion to the iridium, which affects the recovery of the iridium, and the iridium finished product finally obtained is less.
[0091] By comparing Example 1 with Comparative Example 1, it can be seen that a lot of iridium products are finally obtained in Comparative Example 1, but the purity does not meet the requirements at all. This is because, if no carbonization treatment is performed, the yttrium-stabilized zirconia is difficult to dissolve during acid dissolution, resulting in a lot of first filter residue, and the subsequent reaction with sodium hydroxide cannot be fully reacted, so a lot of substandard iridium products are finally produced.
[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. An iridium recovery method, characterized in that: The following steps are involved: Step 1: crushing and grinding the thermal insulation material containing iridium and zirconium dioxide to obtain powder; Step 2: Mixing the powder and the carbon material to obtain a mixed powder; Step 3: heating the mixed powder under vacuum conditions so that the metal elements except iridium form carbides to obtain a carbide mixture; Step 4: dissolving the carbonized mixture in acid, filtering, and obtaining a first filter residue; the first filter residue contains iridium element.
2. The iridium recovery method according to claim 1, wherein The first filter residue is alkali-melted, acid-leached, and filtered to obtain a second filter residue, which is an iridium finished product.
3. The iridium recovery method according to claim 1, wherein Add alkaline solution to the filtrate obtained by filtration in step 4, adjust the pH value to 2-4, and filter to obtain a first precipitate; the first precipitate contains zirconium element.
4. The iridium recovery method according to claim 3, characterized in that: Acid solution is added to the filtrate from which the first precipitate is removed, and the second precipitate is obtained by filtration; the second precipitate contains yttrium element.
5. The iridium recovery method according to claim 1, characterized in that: The carbon material is hydrophobic graphite; In step 4, the carbonized mixture is poured into a container filled with pure water, the carbonaceous material is removed by decanting and filtering, and then acid dissolution is performed.
6. The iridium recovery method according to claim 1, characterized in that: The mass ratio of the powder to the carbon material is 2 to 6:
1.
7. The iridium recovery method according to claim 1, characterized in that: When acid dissolving, first add a sulfuric acid solution with a mass concentration of 20% to 50%, heat it in a water bath to 60°C to 90°C, and slowly drop a hydrogen peroxide solution with a mass concentration of 30% to obtain a solid-liquid mixture; The solid-liquid mixture is heated to boil, and maintained in a slightly boiling state for not less than 30 minutes, and then cooled and filtered to obtain a first filter residue.
8. The iridium recovery method according to claim 2, characterized in that: The first filter residue is dried, powdered sodium hydroxide is added in a mass ratio of 1:1 to 5, and roasted under air at a temperature of 300° C. to 400° C. for 1 to 3 hours, and then cooled and taken out to obtain a roasted mixture; The roasted mixture was added into hydrochloric acid with a mass concentration of 36% for acid leaching, transferred into a beaker, boiled for 1 to 2 hours, cooled and filtered to obtain a second filter residue.
9. The iridium recovery method according to claim 3, characterized in that: The alkali solution is ammonia water, the mass ratio of the filtrate to the ammonia water is 1:1, and the first precipitate is hydrolyzed and precipitated at a temperature of 40° C. to 80° C., and the first precipitate includes zirconium hydroxide.
10. The iridium recovery method according to claim 4, characterized in that: The acid solution is a 1 mol / L oxalic acid aqueous solution, and a second precipitate is precipitated at a temperature of 60° C. to 80° C., wherein the second precipitate includes yttrium oxalate.
